Lepidoptera collected in S. W. Mongolia during expedition in Mongolian Altai in 2022 (Lepidoptera: Geometridae) - Ilya A. Makhov; Vladimir A. Lukhtanov; Maria S. Vishnevskaya (SHILAP)
An annotated checklist of Geometridae collected in Southwest Mongolia is presented. In total 51 species are recorded. Eight species are recorded as new for the fauna of Mongolia, Alcis depravata (Staudinger, 1892), Holoterpna diagrapharia Püngeler, 1900, Scotopteryx supproximaria (Staudinger, 1892) Cataclysme riguata (Hübner, [1813]), Rhodostrophia crypta Viidalepp & Kostkuk, 2020, Idaea ossiculata (Lederer, 1870), Scopula divisaria (Christoph, 1893), and Casilda consecraria (Staudinger, 1871). Habitus and genitalia are illustrated for these species. Four of them were DNA-barcoded, as well as three other species. Results of DNA barcoding are discussed.